Analisis Kasus Berdasarkan Teori Sosiologi Hukum Pengamen dan Anak Jalanan Di Bawah Umur Terhadap Pasal 34 Undang-Undang Dasar Tahun 1945 - Benny Chandra (Universitas Internasional Batam, 2021)
Batam City is an area located in an area close to other countries. This will certainly trigger rapid growth. However, this also creates a new problem with the emergence of street singers and underage street children crowding the streets of Batam. The presence of street singers and street children in Batam City is a factor that makes the author interested in discussing this research. The conclusion from the case analysis based on the sociological theory of street singers and street children is a form of social inequality that occurs in Batam City. the existence of street singers and street children was found at a red light intersection. By promoting buskers and street children can have a negative impact, one of which can disturb road users. This also has an impact on the economy of the city of Batam and for the people themselves. Singers and street children also have an influence on the orderliness of Batam City. If viewed from the sociological theory of law, cases of street singers and underage street children that occurred in Batam City, there is feedback between social and community morals. In this case the Batam city government has a role in controlling street singers and street children. This is also contained in Mochtar Kusumaatmadja's theory, that the development created by the government can provide protection, education and understanding of religion so that buskers and street children can provide solutions in a better way. Meanwhile, Dumairy's theory explains that there is a concern from the government in eradicating street singers and children. The role of the Batam City government in overcoming braking and street children by providing guidance and coaching through the Batam City Social Service